Evaluación del índice de biofilm dental en niños de 5 a 7 años en el Centro Educativo Cotopaxi en la ciudad de Latacunga. - Fabara Herrera, Madeline Natasha (2017)
Dental Biofilm is an accumulation of bacteria that is firmly adhered to dental structures and other oral surfaces. The etiological factor triggers serious pathologies such as; dental caries and periodontal disease, these pathologies are of greater population incidence. Preventive dentistry avoids diseases that are present in the oral cavity. Therefore, it is necessary to apply various methods to help arousing children are interest in oral hygiene by Biofilm controlling and the correct application of dental brushing techniques. Based on above, the objective of this study was to evaluate the Dental Biofilm in the Educational Centre “CEC” Centro Educativo Cotopaxi, located in the city of Latacunga. To carry out the research, 72 children between 5 and 7 years old were selected for the investigation. Four samples of Biofilm dental index were taken to each child at intervals of seven days according to OLeary. The first example was taken without any warning to measure the initial Biofilm index. The results obtained were 36.73 percent, which represents a high Biofilm index average. Days after some speeches, dynamics and motivational education about oral hygiene and dental brushing were performed with the aim to analyse the next samples. Seven days later an average of 29.2 percent was obtained, 14 and 21 days after 24.65 percent and 19.56 percent respectively concluding that there is a statistically significant reduction in the Biofilm index of 0.007 percent. In addition, is precise to keep in mind that children require motivation in schools and at home to develop an interest in oral health.